Raw soybeans as a protein source for growing cattle - Anderson, S.; Brandt, Robert T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 60-day growth trial with 170 exotic crossbred steers (avg. wt. 626 lbs) was conducted to assess the value of raw soybeans in silage-based diets. Protein supplements were based on 1) urea, 2) urea plus soybean oil (SBO), 3) soybean meal (SBM), 4) SBM plus SBO, 5) rolled (RSB), and 6) whole (WSB) soybeans. Soybean oil was added to treatments 2 and 4 in amounts equivalent to that contributed from raw soybeans. Total diets were 11.5% crude protein. Steers fed SBM gained faster (P<.05) and consumed more feed than those fed RSB or WSB. However, SBO added back to the SBM diet resulted in performance similar to that of steers fed RSB or WSB (P=.47). This suggests that the protein value of SBM and raw soybeans was similar, but that small increments (less than 2% of diet dry matter) of soybean lipid inhibited ruminal diet digestion and(or} utilization. There was no advantage for rolling raw soybeans vs. feeding them whole (P=.45). Costs of gain were urea < raw soybeans < soybean meal.
Keywords: Beef; Raw soybeans; Protein; Growing cattle